ANALISIS KEPENTINGAN STAKEHOLDER DALAM PROGRAM PEMBERDAYAAN MASYARAKAT DI HUTAN DESA NAMO KECAMATAN KULAWI - Wahyu, Wahyu; Golar, Golar; Massiri, Sudirman Dg (Universitas Tadulako, 2019)
This study aims to determine stakeholder interests in community empowerment programs in Namo Village Forest, Kulawi District. This study uses a qualitative method, sampling is done by purposive sampling the number of respondents 8. The analysis used is the analysis of influence and importance. The results showed that the level of influence and interests of stakeholders in community empowerment in Namo Village Forest is very diverse, which can be classified as stakeholders who are in the position of Key Player, Subject, Crowd and Context Setter. The stakeholders are Namo Village Forest Management Institute (LPHD), Central Sulawesi Provincial Forestry Service (DISHUT), HL Palu-Poso BPDAS, Kulawi Forest Management Unit (KPH), Kulawi Community and Village Empowerment Office (DPMD) Sigi, IMUNITAS (NGO), The Jembata Foundation (NGO) and the Namo.No Adat Institution. Stakeholders who play a role in empowerment in the Namo Village Forest are stakeholders from government agencies, private agencies and community leaders. The pattern of stakeholder relationships that occur in the community empowerment program in Namo Village Forest, there are three (3) patterns of stakeholder relationship criteria, namely communication, coordination and cooperation.